Epistemological beliefs and attitudes towards physics and physics learning among Malaysian STEM students in Selangor, Malaysia / Norezan Ibrahim ... [et al.] - Ibrahim, Norezan; Damio, Siti Maftuhah; Zulkipli, Zulinda Ayu; Dalim, Siti Fairuz; Mohd Yusof, Mohammad Mubarrak (Universiti Teknologi MARA, 2022)
The poor achievement of students in STEM related subjects especially physics is considered somewhat less satisfactory mainly due to the learning processes and the students’ epistemological belief towards Physics. The purpose of this study is to evaluate the epistemological beliefs and learning attitudes among Malaysian STEM students in Selangor towards Physics and Physics learning. The study identified 120 Malaysian STEM students who undertook Physics from a few schools in Selangor to participate in this research. This is descriptive quantitative research. In order to monitor their beliefs towards Physics and Physics learning, an instrument called The Physics Epistemological Beliefs & Attitudes Test was developed. A valid and reliable measuring instrument was adapted and modified from two previous well-known and validated tools namely, Colorado Learning Attitudes about Science Survey (CLASS) and Maryland Physics Expectations Survey (MPEX). The findings of the study indicated that Malaysian STEM students possess highly sophisticated epistemological beliefs with the mean score of 72.61% and were favourable in learning Physics with the mean score of 74.29%. In this study, substantial differences in both tests were absent in between male and female students. However, significant differences between Form 4 and Form 5 students in epistemological beliefs as well as learning attitudes existed. Pearson correlation gathered shows that the relationships between the epistemological beliefs and learning attitudes among the students were high, positive and very significant (r = .672, p < .05). The results of this study are vital in conducting effective teaching and learning approaches particularly to upgrade the students’ performance and achievement in Physics at schools. Hence, based on this, it would be interesting to further explore the following aspects of epistemological beliefs which focuses on the learning approach used by the students in schools and higher institutions of learning in Malaysia with different variables.